Thermoplastic Nanofluidic Devices for Biomedical Applications - Weerakoon-Ratnayake, Kumuditha M. (Lab Chip, 2017)
Microfluidics is now moving into a developmental stage where basic discoveries are being transitioned into the commerical sector so that these discoveries can affect, for example, healthcare. Thus, high production rate microfabrication technologies, such as thermal embossing and/or injection molding, are being used to produce low-cost consumables appropriate for commercial applications. Based on recent reports, it is clear that nanofluidics offers some attractive process capabilities that may provide unique venues for biomolecular analyses that cannot be realized at the microscale. Thus, it would be attractive to consider early in the developmental cycle of nanofluidics production pipelines that can generate devices possessing sub-150 nm dimensions in a high production mode and at low-cost to accommodate the commercialization of this exciting technology. Recently, functional sub-150 nm thermoplastic nanofluidic devices have been reported that can provide high process yield rates, which can enable commericial translation of nanofluidics. This review presents an overview of recent advancements in the fabrication, assembly, surface modification and the characterization of thermoplastic nanofluidic devices. Also, several examples in which nanoscale phenomena have been exploited for the analysis of biomolecules are highlighted. Lastly, some general conclusions and future outlooks are presented.